Journalists' perceptions about regulation and conflicts in their work: the case of Madrid-based news professionals - García-Avilés,Jose A. (2014)
This study attempts to analyze how journalists from companies based in Madrid (Spain) perceive the main problems they face in their work and their views about media regulation. Using both quantitative and qualitative methods, our research shows Madrid-based media professionals' perceptions about the conflicts and the obstacles they face in their daily work tend to be quite pessimistic. They emphasize the companies' need to achieve profits and the lack of ethical leadership at the management level as their main problems, and they also increasingly advocate for more external media regulation.